PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN DENGAN LOYALITAS PASIEN SEBAGAI VARIABEL MEDIASI PADA RUMAH SAKIT UMUM DAERAH RIAU - Kurniawan, Teuku Reza; Herman, Herman; Wicara, Dinda Genta; Rofidah, Siti (Jurnal Daya Saing, 2025)
Patient satisfaction in health services is found to be low and is one of the determinants of patient loyalty so that the impact of satisfaction will result in patient loyalty. This study aims to analyze the factors that influence patient satisfaction. Methods: used in this research is descriptive and quantitative with 150 respondents who underwent care and treatment at the Pekanbaru City Regional General Hospital. The variables studied were Service Quality, Patient Satisfaction and Patient Loyalty. To measure the variables studied, a questionnaire was used. Path analysis is used to analyze the relationship between variables. Results: the study found 1) The results showed that service quality at the Pekanbaru Regional Hospital significantly increased patient loyalty, with a P-Value of 0.000 and T-Statistics 11.342. 2) The results showed that the quality of service at the Pekanbaru Regional Hospital significantly affected patient satisfaction, with a P-Value of 0.000 and T-Statistics of 14.437. 3) The results showed that patient satisfaction at the Pekanbaru Regional Hospital significantly influenced patient loyalty, with a P-Value of 0.004 and T-Statistics 2.840. 4) The results showed that service quality in Pekanbaru Regional Hospital significantly influenced patient loyalty through patient satisfaction, with a P-Value of 0.008 and T-Statistics 2.605